2018
DOI: 10.1002/mgg3.469
|View full text |Cite
|
Sign up to set email alerts
|

miR‐34a/BCL‐2 signaling axis contributes to apoptosis in MPP+‐induced SH‐SY5Y cells

Abstract: miR-34a and its target gene, BCL-2, play a possible role in the induction of apoptosis in DA neurons, and therefore, they have a potential role in the pathogenesis of PD. Consequently, the therapeutic potential of miR-34a could be considered in order to inhibit the progression of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Previous studies reported that miR-34a re-expression could repress proliferation and promote apoptosis by regulation of Bcl-2 29,30. Since the aforementioned results revealed that ISOV reduced the expression of Bcl-2 protein in vivo, we examined if the effects of ISOV on proliferation, apoptosis and stem-like features of OSLCs were involved in the regulation of Bcl-2 by miR-34a.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies reported that miR-34a re-expression could repress proliferation and promote apoptosis by regulation of Bcl-2 29,30. Since the aforementioned results revealed that ISOV reduced the expression of Bcl-2 protein in vivo, we examined if the effects of ISOV on proliferation, apoptosis and stem-like features of OSLCs were involved in the regulation of Bcl-2 by miR-34a.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, the exact mechanism by which ISOV promotes apoptotic cell death in OSLCs has not been clarified. Considering that Bcl-2, a mitochondrion-associated anti-apoptotic protein, was directly regulated by miR-34a,2830 the purpose of the present study was to examine th e in vivo and in vitro multiplication inhibitory activities and the corresponding apoptosis inducing effects of ISOV in OSLCs. Furthermore, we aimed to investigate the potential mechanisms associated with these processes, notably with regard to the involvement of epigenetic regulations in OS cells.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of microRNA expression showed the downregulated profile of miR-34bc associated with pathological brain tissue in different clinical stages of PD [37,74]. Although reduction of miR-34bc expression in differentiated dopaminergic neuronal cells results in a moderate reduction in cell viability, it was accompanied by altered mitochondrial function [75]. DJ1 and Parkin were also shown to be miR-34bc indirect targets [74].…”
Section: Brain Pathology and Micrornasmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f (Carro et al, 2010;Mi et al, 2018;Packer et al, 2008;Schonrock et al, 2012;Schraivogel et al, 2011;Song et al, 2013;X. Tan et al, 2012) miR-34abc GBM, PD, AD (Leone et al, 2017;Mi et al, 2018;Min˜ones-Moyano et al, 2011;Modi et al, 2015;Navarro & Lieberman, 2015;Shanesazzade et al, 2018) miR-29 GBM, PD, AD, HD (Ihle & Abraham, 2017;Morita et al, 2013;Roshan et al, 2014;Saito & Saito, 2012;Tumaneng et al, 2012) miR-124 GBM, PD, HD (An et al, 2013;Conti et al, 2012;Fowler et al, 2011;Johnson & Buckley, 2009;Makeyev et al, 2007;Mucaj et al, 2014;Saraiva et al, 2016;Silber et al, 2008;Xie et al, 2012) miR-128 GBM, PD, AD, MS oxidative response (Rostamian et al, 2018;Schonrock et al, 2012). Upregulation of miR-9 has been associated with PD and AD pathology with its pro-apoptotic functions.…”
Section: Disorder Mirnasmentioning
confidence: 99%
“…In general, miR-34bc was downregulated in PD. In dopaminergic neurons downregulation of miR-34bc along with mitochondrial dysfunction caused cellular J o u r n a l P r e -p r o o f death (Shanesazzade et al, 2018). Considering the facts, miR-34abc could be a potent therapeutic target in different brain pathologies.…”
Section: Mir-34abcmentioning
confidence: 99%